2019
DOI: 10.1080/09540105.2019.1687658
|View full text |Cite
|
Sign up to set email alerts
|

Development of a colloidal gold immunoassay for the detection of four eugenol compounds in water

Abstract: A monoclonal antibody (mAb), 2C9, selective for four eugenol compounds, was developed based on the eugenol derivatives (Eug-1). The semi-inhibitory concentrations (IC 50) of this antibody against eugenol, isoeugenol, methyl eugenol, and methyl isoeugenol were 0.043, 0.302, 0.016, and 0.082 μg/mL, respectively, and the detection limits (LOD) were 0.012, 0.070, 0.004 and 0.024 μg/mL. With the exception of isoeugenol, which had cross-reactivity of less than 15%, the cross-reactivity of the other compounds was goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Correspondingly, it was observed that the band of the preS2Ag-BSA in SDS-PAGE moved more slowly compared with BSA (Figure 2b), indicating that the molecular weight increased after coupling and confirming the coupling of preS2Ag and BSA. Similar migration rate changes of the conjugate in SDS-PAGE analysis were reported by Shen et al [30]. The unconjugated preS2Ag did not show any band, because the molecular weight was too small (3.3 kD) to remain in the gel.…”
Section: Characterization Of Conjugated Antigensupporting
confidence: 85%
“…Correspondingly, it was observed that the band of the preS2Ag-BSA in SDS-PAGE moved more slowly compared with BSA (Figure 2b), indicating that the molecular weight increased after coupling and confirming the coupling of preS2Ag and BSA. Similar migration rate changes of the conjugate in SDS-PAGE analysis were reported by Shen et al [30]. The unconjugated preS2Ag did not show any band, because the molecular weight was too small (3.3 kD) to remain in the gel.…”
Section: Characterization Of Conjugated Antigensupporting
confidence: 85%
“…The lateral-flow immunochromatographic strip (LF-ICS), is a novel detection method combining nanoparticles and enzyme-linked immunosorbent assay (ELISA) and is simpler and faster than ELISAs. To date, it has been successfully applied to the detection of several anesthetics, such as procaine (Hao et al, 2018), morphine (Chen et al, 2019), and eugenol (Shen et al, 2019). To the best of our knowledge, however, there are no studies using immunoassay methodologies to detect TMS residues.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method is considered to be more sensitive than GC/MS methods, 8,9) HPLC-UV methods, [10][11][12] another HPLC-FL method using derivatization with NBD-COCl, 19) and an ELISA method. 16) Our method is comparable to the LC-MS/MS method for Eug, 15) but is less sensitive for MeEug. 14) However, the proposed method does not require expensive instruments and laboratory equipment for sample pretreatment.…”
Section: Separation Of Dib-derivatives Of Eugsmentioning
confidence: 93%
“…Several analytical methods have been reported for the determination of Eugs, including GC/MS, [7][8][9] HPLC-UV, [10][11][12] liquid chromatography-tandem mass spectrometry (LC-MS/MS), [13][14][15] and enzyme-linked immunosorbent assay (ELISA) 16) methods. Although GC/MS, LC-MS/MS, and ELISA methods are sensitive, sample pretreatment is complicated such as solid-phase extraction for clean-up or the required equipment is expensive.…”
Section: Introductionmentioning
confidence: 99%